Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/4771113
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Industry-University-Research Cooperation Innovation Network Characteristics on Subject Innovation Performance

Abstract: The automobile industry serves as the primary industry for national development and also enhances manufacturing development strategies. Its source of power comes from the maturity and operational efficiency of the technology innovation network within the industry. Firstly, this paper takes the automobile industry of the Yangtze River Economic Belt as the research object and depicts the topological structure of the 1985–2015 Industry-University-Research Cooperation Innovation Network (IURCIN) from the perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In detail, there are two outstanding research teams whose influential leaders are Seonaidh Mcdonald and Kannan Govindan, respectively (both are also top collaborated authors). As a result of this, we suggest scholars increase cooperation regarding this topic with others, which is proved useful to enhance research effectiveness and efficiency (Li et al, 2021; Sun et al, 2021).…”
Section: Resultsmentioning
confidence: 86%
“…In detail, there are two outstanding research teams whose influential leaders are Seonaidh Mcdonald and Kannan Govindan, respectively (both are also top collaborated authors). As a result of this, we suggest scholars increase cooperation regarding this topic with others, which is proved useful to enhance research effectiveness and efficiency (Li et al, 2021; Sun et al, 2021).…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, an industry type was another variable that might affect the relationship between knowledge learning and green enterprise innovation. Some enterprises had a strong ability to acquire external knowledge and industry collaboration [29,52], which further affected green enterprise innovation. The research samples were coded into manufacturing enterprises, resource-based enterprises, and green-oriented enterprises in this study.…”
Section: Regulatory Effect Test (1) the Regulatory Role Of The Defini...mentioning
confidence: 99%
“…Some research results showed that enterprises' access to external resources positively impacts green innovation [25][26][27][28]. However, some scholars, from the perspective of the external network, pointed out that the relationship between the external cooperation network depth of enterprises and the green innovation of enterprises are not in a simple linear relationship but an inverted U relationship [29][30][31], and a too-high depth knowledge search would also lead enterprises to rely on strong links with external resources, which would lead to increased opportunism risks for enterprises [32,33], and may not be conducive to enterprise innovation [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, enterprises have begun to cooperate with other enterprises and scientific research institutions [ 15 ] to effectively alleviate the problems existing in enterprise internal innovation [ 16 ] and promote innovation in the industry [ 17 ]. The degree of enterprise innovation is affected by the cooperation with universities and other scientific research institutions, and knowledge plays a moderating role in the relationship between industry cooperation and product innovation [ 18 ]. The number of scientific research institutions has a positive impact on innovation performance [ 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%